The hot hand in the NBA 3-point contest: The importance of location, location, location - Lantis, R.; Nesson, E. (Journal of Sports Economics, 2024)
We investigate the hot hand in the 1986-2019 NBA 3-Point Shooting Contests. Combining repeated shots in a location and shots across locations, the contest mimics game situations without many of the confounding factors. We find that a hot hand exists in the contest, but only for shots within the same location. Streaks of shots increase a hot hand, but only if the player makes his previous shot and has not moved locations. Our results suggest that while a hot hand does exist in basketball shooting, it is only present when shots are taken from the same shooting location.